A Faster Convergence Artificial Bee Colony Algorithm in Sensor Deployment for Wireless Sensor Networks. (3rd October 2013) - Yu, Xiangyu; Zhang, Jiaxin; Fan, Jiaru; Zhang, Tao
In wireless sensor networks (WSN), sensor deployment is one of the main topics for enhancing the sensor's coverage rate. In this paper, by modifying updating equation of onlooker bee and scout bee of original artificial bee colony (ABC) algorithm, a sensor deployment algorithm based on the modified ABC algorithm is proposed. Some new parameters such as forgetting and neighbor factor for accelerating the convergence speed and probability of mutant for maximizing the coverage rate are introduced. Simulation results showed that comparing with the deployment method based on original ABC and particle swarm optimization (PSO) algorithm, the proposed approach can achieve a better performance in coverage rate and convergence speed while needing a less total moving distance of sensors.